AP collagen peptides improve hair growth and quality by promoting human hair cell proliferation and keratin synthesis - Shim, Dabin; Bae, Il-Hong; Chung, Jin-Oh; Mok, Hye-Won; Roh, Jonghwa; Kim, Wangi; Lee, Chang Seok (Archives of Biological Sciences, 2024)
Paper description: Inhibiting apoptosis and inducing proliferation of human hair follicle cells is important for hair production and hair loss prevention. Considering that collagen peptides are structural proteins found in skin substrates and tissues surrounding follicles, hair growth and improvement of the function of AP collagen peptides (APCP) were evaluated in vitro. APCP exerts proliferative effects, inhibits apoptosis, and increases the expression of antioxidant enzymes and keratin in hair cells. The effect of APCP on human hair cells was revealed for the first time, suggesting that APCP could be an effective bioactive supplement with the potential to improve hair growth and quality. Abstract: Hair is an essential protective and health-maintaining covering for the body, especially the scalp. It is also important esthetically in modern society, where hair loss, whether caused by the severe scalp condition androgenic alopecia or other internal or external factors, has societal and psychological impacts. Preventing the apoptosis of human hair follicle cells, including hair follicle dermal papilla cells (HFDPCs) and human hair follicle keratinocytes (HHFKs), is crucial for hair production, alongside hair strengthening, which is essential in combatting hair loss. Given the structural importance of collagen peptides in the skin matrix and tissues surrounding hair follicles, we studied the function of AP collagen peptides (APCP) as a hair growth and quality improvement agent. APCP was found to stimulate the proliferation of hair follicle cells and counteract H2O2-induced apoptosis. It also significantly suppressed the expression of dickkopf-1 (DKK1) and bone morphogenetic protein 6 (BMP6), which induce hair cell apoptosis in the presence or absence of UVA/B irradiation. Moreover, APCP induced expression of the antioxidant enzymes, catalase and superoxide dismutase 1 (SOD1), while enhancing hair keratin expression in HHFKs. Mechanistically, APCP facilitated hair growth by elevating GAS6 expression and activating PKA and AKT/ERK signaling pathways. Notably, APCP increased levels of phosphor-β-catenin (Ser552/Ser675) as well as total β-catenin, as demonstrated by Western blotting and immunocytochemistry. Lastly, we showed that APCP increased expression of the hair cuticle type I keratins, keratin-32 and 42, in HHFKs. Overall, these findings propose APCP as a promising candidate for safeguarding hair follicle cells and mitigating hair loss by improving hair growth and quality.